2019
DOI: 10.3390/brainsci9010014
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms Underlying the Deleterious Effects of Synthetic Cannabinoids Found in Spice/K2 Products

Abstract: The chief psychoactive constituent of many bioactive phytocannabinoids (Δ9-tetrahydrocannabinol, Δ9-THC) found in hemp, cannabis or marijuana plants are scientifically denoted by the Latin term, Cannabis sativa, acts on cell surface receptors. These receptors are ubiquitously expressed. To date, two cannabinoid receptors have been cloned and characterized. Cannabinoid receptor type 1 (CB1R) is found to serve as the archetype for cannabinoid action in the brain. They have attracted wide interest as the mediator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…79 Subsequently, azaindole 19 was found in herbal blends in Germany in 2016 80 and 2017. 81 Following the discovery of a clandestine SCRA manufacturing facility in the Hubei Province of China, NNL-1 (20) was identified and reported in 2016. 82 pyridine) nucleus.…”
Section: Azaindolesmentioning
confidence: 99%
See 2 more Smart Citations
“…79 Subsequently, azaindole 19 was found in herbal blends in Germany in 2016 80 and 2017. 81 Following the discovery of a clandestine SCRA manufacturing facility in the Hubei Province of China, NNL-1 (20) was identified and reported in 2016. 82 pyridine) nucleus.…”
Section: Azaindolesmentioning
confidence: 99%
“…Since 2008, multiple cases of morbidity and mortality, which are not typically observed following the consumption of cannabis, have been associated with the recreational use of products containing indole and/or indazole SCRAs. For example, over the course of one week in July 2017, approximately 158 people in Lancaster County, Pennsylvania, United States, presenting with varying symptoms ranging from hypotension to unconsciousness, were treated for SCRA‐related overdose .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STS‐135 is an extremely potent, third generation SCB with anecdotal evidence indicating that very little of the compound is required to generate a physiological response . Currently, there is only one study that investigated and reported metabolism of STS‐135.…”
Section: Discussionmentioning
confidence: 99%
“…STS-135 is an extremely potent, third generation SCB with anecdotal evidence indicating that very little of the compound is required to generate a physiological response. 12,19 Currently, there is only one study that investigated and reported metabolism of STS-135. According to the publication, two major hepatic metabolites of STS-135 are M25 and M21, which are mono-and di-hydroxilated metabolites, which suggests that CYPs are the major class of enzyme responsible for the oxidative metabolism of this compound.…”
Section: Discussionmentioning
confidence: 99%